À propos de la politique routière de l’État romain : l’apport des fouilles d’Ambrussum (Villetelle, Hérault) - Jean-Luc Fiches (Gallia)
The extensive excavations of the Ambrussum relay station (Villetelle, Hérault), established at the foot of the oppidum around 25 BC, seek to determine the functions of its various sections. To date, milestones, bathhouses, a blacksmith’s house and forge, and an area set aside for worship have been identified. The article focuses on a range of elements that suggest the role of the Roman state in its existence. It appears that, through a series of subdivisions, Rome fostered the development of this station from the beginning of the Empire. It then added several buildings that could have been staging posts of the Imperial Mail. These were in turn replaced in the 4th century by a new public edifice based a different layout, approximately at the time when the Itinerarium Burdigalense referred to Ambrussum as a mutatio, after the settlement was abandoned. Moreover, its role in the manufacture of arms, as attested to in the first half of the 2nd century, suggests the presence of a small garrison.